2010
DOI: 10.1002/ajmg.b.31006
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence of ubiquitin proteasome system dysregulation in schizophrenia and bipolar disorder: Convergent pathway analysis findings from two independent samples

Abstract: Schizophrenia (SCZ) and bipolar disorder (BPD) are polygenic disorders with many genes contributing to their etiologies. The aim of this investigation was to search for dysregulated molecular and cellular pathways for these disorders as well as psychosis. We conducted a blood-based microarray investigation in two independent samples with SCZ and BPD from San Diego (SCZ = 13, BPD = 9, control = 8) and Taiwan (SCZ = 11, BPD = 14, control = 16). Diagnostic groups were compared to controls, and subjects with a his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 34 publications
2
78
0
Order By: Relevance
“…Abnormalities of ubiquitin gene expression have been reported in blood cells and the HC, PFC, and temporal gyrus of patients with schizophrenia (77)(78)(79). Gene sets related to the ubiquitin proteasome system have also been identified in two pathway analytical studies of schizophrenia, providing further evidence for the involvement of the ubiquitination processes in disease etiology (80). This is consistent with a growing number of studies suggesting that ubiquitin genes may function as upstream factors impacting the disturbed synaptic plasticity process reported in schizophrenia (81).…”
Section: Resultsmentioning
confidence: 94%
“…Abnormalities of ubiquitin gene expression have been reported in blood cells and the HC, PFC, and temporal gyrus of patients with schizophrenia (77)(78)(79). Gene sets related to the ubiquitin proteasome system have also been identified in two pathway analytical studies of schizophrenia, providing further evidence for the involvement of the ubiquitination processes in disease etiology (80). This is consistent with a growing number of studies suggesting that ubiquitin genes may function as upstream factors impacting the disturbed synaptic plasticity process reported in schizophrenia (81).…”
Section: Resultsmentioning
confidence: 94%
“…Interesting genes with suggestive evidence for association include CSMD1, a gene previously implicated in large GWAS of other psychiatric disorders (Schizophrenia Psychiatric Genome-Wide Association Study, 2011), genes (JAK1, FASLG) related to immune response, a pathway that has previously been implicated for PTSD by GWAS (Guffanti et al, 2013) as well as gene expression studies (Glatt et al, 2013), and genes (UBE2E3, UBE2U) from the ubiquitin system, which has been implicated in the etiology of schizophrenia and bipolar disorder (Bousman et al, 2010). Before conclusions can be drawn however these genes must be replicated in larger GWASs and meta-analyses currently planned by the PGC PTSD working group (Koenen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of this disorder remains unclear, although research strongly points towards the interaction between genetic and environmental influences (Tsuang, 2000;Aukes et al, 2008). Recent gene expression and protein studies have reported an alteration of ubiquitin pathways in the brains from schizophrenia sufferers compared to controls (Bousman et al, 2010;Rubio et al, 2013).…”
Section: Introductionmentioning
confidence: 99%